Influence of host plants and soil diluents on arbuscular mycorrhizal fungus propagation for on-farm inoculum production using leaf litter compost and agrowastes - Amornrat Chaiyasen (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Increasing costs and predicted exhaustion of readily-recoverable P fertilizers strongly encourage farmers to make deliberate use of the arbuscular mycorrhizal (AM) symbiosis. Three experiments were conducted to select suitable host plants and agrowaste diluents for on-farm inoculum production. AM fungi (Claroideoglomus etunicatum NNT10, C. etunicatum PBT03 and Funneliformis mosseae RYA08) first were propagated using different culture materials (sterile sandy soil by itself or mixed 1:1 (v/v) with clay-brick granules, rice husk charcoal or vermiculite) and host plants (Mimosa invisa, Sorghum bicolor or Zea mays) in a greenhouse. Root colonisation and spore number of each AM fungus isolate were affected by host plant and substrate. Overall, spore population and root colonisation were highest when using Z. mays (3690 spores 100 cm−3and 65% root length colonised) and vermiculite (3612 spores, 100 cm−3and 63%). A subsequent survey experiment in a scaled-up on-farm system using the pooled inoculum produced in the greenhouse and a variety of host plants resulted in Z. mays being selected for the final experiment. The final experiment examined production of inoculum outdoors in large containers containing starter inoculum mixed with leaf litter compost, sand, and either vermiculite or one of the locally-available agrowastes oil palm bunches, stunted rice or wood chips. Results showed AM fungus spore production with oil palm bunches to be equivalent to that with the more expensive, imported vermiculite. The results indicate that leaf litter compost and oil palm bunches are suitable farm wastes for the on-farm production of AM fungal inoculum.